The use of antenatal fetal magnetic resonance imaging in the assessment of patients at high risk of preterm birth. (March 2018) - Story, L.; Hutter, J.; Zhang, T.; Shennan, A.H.; Rutherford, M.
Abstract: Preterm birth, defined as birth occurring prior to 37 weeks gestation is a common obstetric complication affecting 8% of pregnancies and is associated with significant morbidity and mortality. Infection/inflammation has been implicated in both the aetiology of preterm birth itself and associated neonatal pulmonary and neurological morbidity. Treatment options are currently limited to prolongation of the pregnancy using cervical cerclage, pessaries or progesterone or administration of drugs including steroids to promote lung maturity and neuroprotective agents such as magnesium sulphate, the timing of which are highly critical. Although delivery is expedited in cases of overt infection, decisions regarding timing and mode of delivery in subclinical infection are not clear-cut. This review aims to explore the use of magnetic resonance imaging (MRI) in the antenatal assessment of pregnancies at high risk of preterm birth and its potential to guide management decisions in the future.